Analisis Peran Balai Benih Ikan (BBI) Kecamatan Lubuk Pakam Dalam Meningkatkan Kesejahteraan Masyarakat - Devi safitri; Nurbaiti Nurbaiti (JURNAL RISET RUMPUN ILMU HEWANI, 2024)
The Fish Seed Center (BBI) in Lubuk Pakam Subdistrict, as a government representative, is expected to advance the welfare of the community through business opportunities in the fisheries sector involving several villages geographically. The research problem formulation encompasses the role of BBI in improving the welfare of the community in Sumber Jaya Subdistrict and its economic contributions. The objectives of this study are to understand the role of BBI in improving the welfare of the community in Lubuk Pakam Subdistrict and to analyze the Islamic economic perspective regarding BBI’s role in enhancing community welfare. This research employs a qualitative approach, gathering primary data through interviews, questionnaires, observations, and secondary data through documentation. The research population includes 49 individuals, and the entire population is considered the sample due to its size being less than 100, making this a population study.